Structure of the Assynt window, Moine Thrust Zone and relationship of thrusts to alkaline igneous complexes, Caledonian orogeny, NW Scotland - Searle, MP (Cambridge University Press, 2023)
The Moine Thrust Zone forms the Caledonian orogenic thrust front where the Moine Supergroup metamorphic rocks have been thrust westward across the Laurentia plate stable foreland, comprising Archean-Proterozoic granulite and amphibolite facies rocks (Lewisian gneisses), with unconformably overlying Mesoproterozoic and Neoproterozoic Torridonian clastic sediments and Cambrian-Ordovician passive margin sedimentary rocks. Four major thrusts beneath the Moine thrust in the Assynt window include the (i) Ben More Thrust, which places the Loch Ailsh syenite intruded into Lewisian basement and Cambrian-Ordovician sedimentary rocks over the Sole thrust sheet, (ii) Glencoul thrust, which places Lewisian basement and folded cover rocks over Cambrian-Ordovician sedimentary rocks, (iii) Borralan thrust, which carries a large alkaline syenite intrusion beneath the Ben More roof thrust and (iv) the Sole thrust sheet, which carries imbricated Cambrian-Ordovician sedimentary rocks and lamprophyre sills over the stable foreland. Three further thrust sheets within the Lewisian basement gneisses are now recognised through restoration of balanced cross-sections, which were responsible for doming of the Assynt window. Although the Moine thrust is mapped as a single line on the map it encompasses, (a) deep ductile shear zone formed of mylonites derived from hangingwall Moine schists, footwall Cambrian quartzites and Ordovician limestones, and basement Lewisian gneisses, (b) roof thrust of the Glencoul and Ben More Thrust sheets and (c) brittle out-of-sequence motion where the Moine schists have been thrust over mylonites, which directly overlie the stable foreland (Knockan Crag).